Monitoring Heart Condition of the Patient with ECG Sensor - Azmi, Muhamad Afiq; Baharuddin, Elfarizanis (Evolution in Electrical and Electronic Engineering, 2023)
This work is about heart rate monitoring system which can give immediate response to patient suffer for heart disease in their own house and have time for them to refer their disease in a hospital. Mostly, that there is no early detection for heart disease patients that could save their lives if normal heartbeat and an abnormal heartbeat can be compared. An abnormal ECG can signal a medical emergency, such as a myocardial infarction heart attack or a dangerous arrhythmia. Next, the heart patients cannot go to the hospital on their own. In most cases, the symptom will begin slowly, however sometimes the symptoms can be sudden and intense. Electrocardiogram is a famous heart rate monitoring machine in many public or private hospital with its ability to measure and record vital sign of heart patient clearly and continuous. The system is about self-monitoring and using an AD8232 sensor to monitor electrocardiography (ECG) signals. ECG is a non-invasive method of measuring the electrical activity of the heart and is widely used in medical settings for diagnosis and treatment of cardiovascular diseases. The AD8232 is a low-cost, single-lead ECG sensor that can be easily integrated into wearable or portable devices for continuous monitoring of ECG signals. With the help of Ad8232 sensor and Arduino UNO, it can measure heart rate and Electrocardiogram and analyze it with help of Excel data streamer and MATLAB. The sensor data display the result in ECG graph and in beats per minute (BPM) and display it to the TFT LCD. The recorded ECG signals are analyzed using standard techniques such as filtering, peak detection, and heart rate calculation. The results demonstrate the feasibility of using an AD8232 sensor for continuous, real-time monitoring of ECG signals, and highlight the potential of this approach for applications in telemedicine and remote healthcare.